Heat treatment effect of MoO3 on the MB removal and its reuse. (October 2018) - Santos-Beltrán, A.; Santos-Beltrán, M.; Paraguay-Delgado, F.; Fuentes, L.; García, R.; Orozco, V. Gallegos
Abstract: Microstructural change and MB removal tests were studied of MoO3 as a function of heat treatment. Synthesized materials were mill and stabilize it structure for MB removal by milling and heating process. It was found that the optimized material can be reused cyclically, obtaining always 100% of the MB removal. Around 90% of MB removal was reached in ∼30 min. The removal process has not influence by UV-Vis illumination, it works by adsorption. Morphology and microstructure were studied by electron microscopy techniques and XRD techniques. By infrared spectroscopy was characterize the material for recycling process on MB removal. XRD patterns were refine by Rietveld method to determine lattice parameters, percentage of phases, crystal sizes and anionic vacancies concentration. The thermal stability of materials was study by thermogravimetric analysis and differential scanning calorimetry. Optimized material could be reused to MB removal. Graphical abstract: Image 1 Highlights: In situ microstructural analysis of orthorhombic and hexagonal MoO3 as a function of temperature. Getting orthorhombic MoO3 nanoparticles by calcination process and subsequent mechanical milling. Elimination of low concentrations of methylene blue by MoO3 nanoparticles in a relatively short time in the absence of light. The MoO3 nanoparticles can be reused cyclically obtaining approximately 100% of the methylene blue removal.